Research gaps in the demography of aging with disability - Freedman, Vicki A. (Disability and health journal, 2014)
The evidence base regarding the demography of aging with disabilities in the US is growing yet substantial gaps remain. This paper summarizes seven major research gaps identified during a conference held in May 2012: how many adults are aging with disabilities; has survival improved for individuals aging with disabilities; can the notion of active life expectancy help inform understanding of aging with disability; what is the pattern of onset of secondary conditions for individuals aging with disabilities and how might such conditions be prevented and/or their debilitating effects ameliorated; what role has obesity had in shaping the population of individuals aging with disability; how do individuals aging with disability differ from those who develop disability later in life; and what are the long-term consequences of developing disability before late life for subsequent health, functioning, and socioeconomic outcomes. Bridging these gaps is crucial for enhancing understanding of this understudied population.